Zmiana modelu nauczania studentów... - Curry, Jane (Horyzonty Wychowania, 2017)
American higher education has begun a shift from professorsdelivering information to students to faculty as facilitators andassessors of student learning. The process of opening up forstudents to learn by doing and discovering has not only begunto change how education is done but has also created tensions.In this process, Jesuit-Catholic education has added extradimensions.